Intestinal obstruction due to small bowel volvulus - Maharjan, Suresh; Thapa, Kaushal Samsher; Shakya, Niliza; Ghimire, Sabin Kumar; Baruwal, Anuj (International Surgery Journal, 2024)
Primary small bowel volvulus is very rare and has feature of intestinal obstruction. Patient usually has unviable segment of bowel with need of resection intra-operatively. In our case report we present case of 88 years male presented in emergency department with features of bowel obstruction and pre-operative abdominal x-ray showed small bowel obstruction followed by CT scan which revealed small bowel volvulus at terminal ileum. Exploratory laparotomy was done and with untwisting of involved segment without need of resection and patient was discharged uneventfully with normal post-operative recovery and follows up also showed no any issue.